MORAL CONFLICT IN FYODOR DOSTOEVSKY’S “CRIME AND PUNISHMENT” - Abatbaeva Uldaulet (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article explores the moral conflict in Fyodor Dostoevsky’s novel Crime and Punishment, analyzing the psychological and philosophical struggles of Rodion Raskolnikov. The study examines his theory of extraordinary individuals, his crime, and the resulting guilt, fear, and spiritual suffering. Special attention is given to Sonia Marmeladova, a symbol of morality and redemption, and other key characters who influence Raskolnikov’s transformation. This research highlights the relevance of the novel in modern society and underscores the significance of moral conscience and responsibility. Findings demonstrate that ethical conflict drives the narrative, revealing the tension between good and evil inherent in human nature.